Al-Farabi: Filsafat Emanasi, Ketuhanan, Kenabian, Jiwa dan Akal - Syofrianisda, Syofrianisda; AM, Rusydi; Saputra, Riki (El-Rusyd, 2024)
Al-Farabi's thought on divinity is one of the main pillars of the Islamic philosophical tradition, which sought to harmonize Islamic revelation with Greek philosophy, especially Aristotle and Plotinus. Al-Farabi viewed God as the First Cause (al-'Illah al-Ula), which is the origin of all existence through emanation (al-faith). This concept places God as the transcendent, perfect, infinite Being and the source of all reality. This article explores how Al-Farabi formulated the relationship between God, reason, and the universe, and highlights his attempts to explain the nature of divinity with a rational approach. In this exploration, several important issues are raised, such as the harmony between reason and revelation, God's relationship with the universe through emanation, and how God's nature can be understood without diminishing His transcendence. In addition, this study also discusses the implications of Al-Farabi's thought for Islamic theology and its relevance in the modern context. Using a literature analysis approach to Al-Farabi's major works, such as Al-Madina al-Fadila and Kitab al-Huruf, this study found that Al-Farabi sought to provide a harmonious synthesis between philosophical traditions and religious beliefs, although his concepts often sparked theological debates. The findings confirm that Al-Farabi's thought has a significant contribution in shaping Islamic philosophical discourse, especially in understanding the relationship between God, reason and reality.